Potential Roles of miRNAs in Acute Rejection for Vascularized Composite Allotransplantation - Li H; Fang Y; Li X; Chen J; Xiong Y; Shi Y; Li S; Ye L; Wang S; Zhou J (Dove Medical Press, 2022)
Haibo Li,1,2,* Yuan Fang,1,2,* Xu Li,2,* Jingting Chen,1 Yao Xiong,1 Yongzhou Shi,3 Shengli Li,1 Lincai Ye,4 Shoubao Wang,1,* Jianda Zhou2,* 1Department of Plastic and Reconstructive Surgery, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China; 2Department of Plastic Surgery, The Third Xiangya Hospital, Central South University, Changsha, People's Republic of China; 3Department of Neurosurgery, Neihuang Chinese Medicine Hospital, Anyang, People's Republic of China; 4Department of Thoracic and Cardiovascular Surgery, Shanghai Children's Medical Center, Shanghai Jiaotong University School of Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Shoubao Wang; Jianda Zhou, Email wxldragon198418@163.com; zhoujianda@csu.edu.comAim: The development of microsurgery has greatly advanced vascularized composite allotransplantation (VCA). However, like organ transplantation, VCA is also limited by acute rejection, and concerns regarding long-term survival and function of the transplanted graft. Therefore, it is necessary to elucidate the molecular mechanisms underlying acute rejection caused by VCA, in order to improve patient survival.Methods: Firstly, we used Brown Norway rats and Lewis rats to construct animal model of VCA. Regularly record the appearance changes of all subjects. Specimens were collected for histological examination, microRNAs (miRNAs) sequencing and RT-qPCR verification when acute immune rejection occurred. Then, bioinformatics analysis was employed to predict miRNA related molecules and pathway information. Finally, differentially expressed miRNAs were tested and verified.Results: MiRNAs are small non coding RNA transcripts that regulate gene expression at the post-transcriptional level. Studies have shown that miRNAs are involved in immune regulation and several miRNAs have been identified that are potential diagnostic and prognostic biomarkers of acute rejection. In this study, we found that the expression levels of rno-miR-21-5p, rno-miR-340-5p, rno-miR-1-3p and rno-miR-195-5p are significantly associated with acute rejection following VCA.Conclusion: This miRNA signature can potentially an auxiliary diagnostic indicator of rejection, which can help clinicians adjust the immunosuppressive program in time during acute rejection.Keywords: vascularized composite tissue allograft1, VCA2, miRNAs4, acute rejection5